2000
DOI: 10.1128/jvi.74.24.11977-11982.2000
|View full text |Cite
|
Sign up to set email alerts
|

The K-bZIP Protein from Kaposi's Sarcoma-Associated Herpesvirus Interacts with p53 and Represses Its Transcriptional Activity

Abstract: Kaposi's sarcoma-associated herpesvirus (KSHV) is a gammaherpesvirus that has been implicated in the pathogenesis of Kaposi's sarcoma. KSHV encodes K-bZIP (open reading frame K8), a protein that belongs to the basic region-leucine zipper (bZIP) family of transcription factors. Here we show that K-bZIP associates with the cellular transcription factor p53 directly in vitro and in vivo. This interaction requires the bZIP domain of K-bZIP and the carboxy-terminal region (amino acids 300 to 393) of p53. We also sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 73 publications
(63 citation statements)
references
References 33 publications
3
60
0
Order By: Relevance
“…Typically, the tumor response to chemotherapy is dependent upon functional p53. However, an in-depth analysis of p53 function in PEL has been missing, because multiple proteins of the PEL-associated human tumor virus KSHV were shown to inhibit p53 in ectopic expression experiments (27,31,48,55,61,62), thus asserting the dogma that all DNA tumor viruses inactivate p53. If this were true, the presence of KSHV would severely limit the treatment options for PEL and other KSHV-associated cancers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Typically, the tumor response to chemotherapy is dependent upon functional p53. However, an in-depth analysis of p53 function in PEL has been missing, because multiple proteins of the PEL-associated human tumor virus KSHV were shown to inhibit p53 in ectopic expression experiments (27,31,48,55,61,62), thus asserting the dogma that all DNA tumor viruses inactivate p53. If this were true, the presence of KSHV would severely limit the treatment options for PEL and other KSHV-associated cancers.…”
Section: Discussionmentioning
confidence: 99%
“…How, then, can we reconcile these data with reports demonstrating disruption of p53 signaling by lytic and latent KSHV viral proteins? KSHV lytic proteins have been shown to inhibit p53 function through coactivator sequestration (Rta/ORF50) (18,31), repression of ATM-mediated DNA damage signaling (v-IRF) (62), or other unknown mechanisms (K-bZIP) (48). Neither Rta/ORF50, K-bZIP, nor vIRF-1 is expressed during latency in PEL (26).…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports showed that latency-associated nuclear protein 1 (LANA1), K-bZIP, and vIRF3/LANA2 of KSHV interact with p53 and that these interactions result in the repression of p53-mediated transcription and apoptosis (3,16,21). Recently, Rivas et al (21) reported that KSHV LANA2 is a B-cell-specific latent viral protein and that it inhibits p53.…”
Section: Vol 75 2001mentioning
confidence: 99%
“…13,14) pISRE-Luc contains interferon stimulated response elements, pG-13-Luc contains synthetic p53 response elements. 15,16) Plasmid cytomegalovirus (pCMV)-RL (Renilla luciferase) was used to evaluate the control transcription. We found that AIF deregulated AP-1-and NF-kB-dependent transcriptions (Fig.…”
Section: Alpinumisoflavone Inhibits the Cell Viabilitymentioning
confidence: 99%